The Effect of Spiral Inducing Chamber on Left Ventricular Assist Device Outflow Cannula - Thomas, Siti Aisyah; Md. Khudzari, Ahmad Zahran; Osman, Kahar; Dillon, Jeswant; Taib, Ishkrizat (International Journal of Integrated Engineering, 2022)
The rise of heart failure in the setting of shortage heart donor had brought to the emergence of development of left ventricular assist device (LVAD). However, patients are still encountering severe complications such as stroke and device thrombosis due to the hemodynamic changes. This study aimed to compare the hemodynamic characteristic between the standard and spiral LVAD outflow cannula. Two different anastomosis sites (2cm and 3cm) from sino-tubular junction are used and a spiral inducing chamber is attached to the cannula to promote spiral flow. The result showed that spiral LVAD cannula exhibit a lower output velocity with 37% percentage difference and lower region of low WSS value.